Flexural Strengthening of Damaged T-Joists with Severe Corrosion Using CFRP Sheets - Jose Vercher; Enrique Gil; Ángeles Mas; Carlos Lerma; M. Eugenia Torner (Advances in Materials Science and Engineering)
This paper evaluates the residual safety of isolated T-joists with severe corrosion for the two extreme cases of boundary conditions, simply supported and fixed-ended, in order to help in making decisions about the magnitude of the necessary intervention. When the T-joist is part of a complete slab, the boundary conditions will be in an intermediate situation between these two extreme cases, so that it is possible to assess the safety with respect to its degree of embedding. The research is conducted for the cases of healthy T-joist, T-joist with complete corrosion of the lower reinforcement, and repaired T-joists with a variable number of CFRP sheets. This work is based on the ACI 318 load test to maintain a structure in use and proposes a Load Factor (LF), which estimates the safety reserve. The simply supported T-joists specimens with severe corrosion do not meet the Load Factor or ACI 318 criteria, even with a large number of CFRP sheets. On the other hand, fixed-ended cases can be kept in use despite corrosion by applying light CFRP strengthening, and with four sheets the initial safety is restored.